THE RELATIONSHIP BETWEEN AGE, GENDER, AND BODY MASS INDEX TO THE PREVALENCE OF FLATFOOT IN PRIMARY SCHOOL CHILDREN IN LAWEYAN - Suci Muqodimatul Jannah (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: Flatfoot is is a postural deformity relating to the collapse or flattening of the medial longitudinal arch. It often appears with symptoms and varying degrees of deformity and disability. Flatfoot can be influenced by two factors; internal and external factors. The purpose of this study is to estimate the correlation between age, sex and body mass index (BMI) with the prevalence of flatfoot in primary school children in Laweyan. Methods: This study was an analytic observational study with cross sectional approach. A sample of 285 subjects was obtained through the sample size calculation with the research formula for the proportion of one group. The subjects were 68 students of SDIT Insan Mulia and 217 students of SDIT Nur Hidayah which obtained by stratified random sampling. Inked foot print test and Chippaux Smirak Index were used to identify the flatfoot. Result: There were 172 people (60.4%) experienced flatfoot with the highest number at age 7 years (67.9%) and there was no association between age and flatfoot (p>0.05). The prevalence of flatfoot was higher in male than female and 78.7% of obese children had flatfoot with p<0.05. The prevalence of flatfoot grade 1, grade 2, and grade 3 were 82%, 11%, and 6,4% respectively. Conclusion: There was correlation between gender and BMI with flatfoot, but there was no correlation between age and flatfoot. The association between flatfoot and BMI does not mean BMI is a contributing factor to the occurrence of flatfott in children. Keywords: Age, gender, BMI, flatfoot